Electroencephalography (EEG) Features in Patients with Primary Headache at Neurology Polyclinic of Dr. M. Djamil Padang Hospital - Susanti, Restu (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2020)
Headache is one of the most common neurological complaints. The InternationalHeadache Society (IHS) classification divides headaches into a primary and secondaryheadache. The cause or type of headache can be determined from the history of thedisease and physical examination. Neurophysiological tests are used in establishing adifferential diagnosis of headache. There are several neurophysiological methods usedin the diagnosis of headaches, one of them is electroencephalography. This study aimsto look at the most frequent EEG picture in cases of a primary headache without focalneurological deficits in the Neurology Polyclinic of Dr. M. Djamil Padang Hospital fromJanuary 2019 to December 2019. This research used a descriptive method. The studypopulation was all patients who underwent an EEG examination in the IntegratedDiagnostic Installation (IDT) of Dr. M. Djamil Padang Hospital from January 2019 toDecember 2019. Subjects were patients who had a chief complaint of headache whohad been subjected to an EEG examination. Statistical analyzes were performedcomputerized using IBM SPSS Statistics version 23.0 for Windows. From this study,the most common chronic headache is migraine, and the most common EEG feature isnormal. EEG can be used as a modality for investigating chronic headaches withoutfocal neurological deficits.